The influence of socio-psychological resources on the adaptation process of people aged 30–55 years in conditions of war stress: empirical substantiation - Pankova, Halyna (Global Prosperity, 2026)
This article examines the influence of psychological resources on the adaptation process of individuals in conditions of wartime stress. The relevance of the study is due to the fact that prolonged military exposure is accompanied not only by increased psycho-emotional stress, but also by the need to preserve the adaptive potential of an adult individual in a situation of chronic uncertainty, loss, and constant threat. The aim of the study was to empirically substantiate the role of socio-psychological resources in ensuring the adaptation of middle-aged individuals in wartime conditions. The study involved 479 respondents aged 30–55 years, with an average age of 47.4±3.6 years. It was found that in both age groups, subclinical manifestations of anxiety and depression prevail, with the average level of anxiety being higher in respondents aged 30–44. The majority of the study subjects were characterized by an average level of resilience and an average level of socio-psychological adaptation. Individuals aged 45–55 demonstrated higher indicators of psychological well-being on the scales of autonomy, control over the environment, personal growth, positive relationships, and purposefulness. Correlation analysis revealed statistically significant relationships between emotional comfort, internal control, adaptability, anxiety, depression, and indicators of post-traumatic growth. It was concluded that the key socio-psychological resources for adaptation in conditions of war stress are emotional comfort, internal locus of control, resilience, psychological well-being, and positive interpersonal relationships.